The Millicent Quibb School of Etiquette for Young Ladies of Mad Science - McKinnon, Kate, 1984- (New York : Little, Brown and Company, 2024)
"Three orphaned siblings become the pupils of the mysterious Professor Millicent Quibb and enter the world of mad science"--
Ages 8-12.
Keywords: Orphans -- Fiction; Sisters -- Fiction; Scientists -- Fiction; Schools -- Fiction